2007
DOI: 10.1016/j.vaccine.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of severe gastroenteritis in pups after canine parvovirus vaccine administration: A clinical and laboratory diagnostic dilemma

Abstract: A total of 29 faecal samples collected from dogs with diarrhoea following canine parvovirus (CPV) vaccination were tested by minor groove binder (MGB) probe assays for discrimination between CPV vaccine and field strains and by diagnostic tests for detection of other canine pathogens. Fifteen samples tested positive only for CPV field strains; however, both vaccine and field strains were detected in three samples. Eleven samples were found to contain only the vaccine strain, although eight of them tested posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 30 publications
3
81
0
3
Order By: Relevance
“…The genetic identity between the 'field' strain 490/07 and the vaccine virus Felocell suggests a possible isolation of the vaccine strain from a cat recently vaccinated. In fact, it is well known that modified-live parvoviruses contained in the vaccines are able to replicate in the intestinal mucosa of vaccinated animals and to be shed with the dog or cat faeces (Decaro et al, 2007;Patterson et al, 2007). In our case, the anamnesis of the cat shedding a Felocell-like FPLV strain was not known, thus preventing the unambiguous identification of strain 490/07 as vaccine virus.…”
Section: Discussionmentioning
confidence: 80%
“…The genetic identity between the 'field' strain 490/07 and the vaccine virus Felocell suggests a possible isolation of the vaccine strain from a cat recently vaccinated. In fact, it is well known that modified-live parvoviruses contained in the vaccines are able to replicate in the intestinal mucosa of vaccinated animals and to be shed with the dog or cat faeces (Decaro et al, 2007;Patterson et al, 2007). In our case, the anamnesis of the cat shedding a Felocell-like FPLV strain was not known, thus preventing the unambiguous identification of strain 490/07 as vaccine virus.…”
Section: Discussionmentioning
confidence: 80%
“…The amino acid residue 440 is important because it is located at the top of the 3-fold spike (GH loop) of the VP2 protein on the surface of the capsid, the main antigenic site of the virus [49,50]. This residue was undergoing positive selection for the past few years and had evolved independently in different populations, which explained its world-wide mutation in unrelated CPV-2 populations [51]. Similar codon change at amino acid position 440 was also reported in CPVs isolated in different countries [28,44,52].…”
Section: Discussionmentioning
confidence: 99%
“…The reports of gastroenteritis subsequent to vaccination are related to infection with CPV field strains shortly before or after the vaccine administration [23]. It has previously been demonstrated that a type 2 vaccine is able to provide protection against type 2a and 2b field isolates [27].…”
Section: Immunizationmentioning
confidence: 99%